Effects of Src Kinase Inhibition on Expression of Protein Tyrosine Phosphatase 1B after Brain Hypoxia in a Piglet Animal Model - Dimitrios Angelis; Maria Delivoria-Papadopoulos (Mediators of Inflammation)
Background. Protein tyrosine phosphatases (PTPs) in conjunction with protein tyrosine kinases (PTKs) regulate cellular processes by posttranslational modifications of signal transduction proteins. PTP nonreceptor type 1B (PTP-1B) is an enzyme of the PTP family. We have previously shown that hypoxia induces an increase in activation of a class of nonreceptor PTK, the Src kinases. In the present study, we investigated the changes that occur in the expression of PTP-1B in the cytosolic component of the brain of newborn piglets acutely after hypoxia as well as long term for up to 2 weeks. Methods. Newborn piglets were divided into groups: normoxia, hypoxia, hypoxia followed by 1 day and 15 days in FiO2 0.21, and hypoxia pretreated with Src kinase inhibitor PP2, prior to hypoxia followed by 1 day and 15 days. Hypoxia was achieved by providing 7% FiO2 for 1 hour and PTP-1B expression was measured via immunoblotting. Results. PTP-1B increased posthypoxia by about 30% and persisted for 2 weeks while Src kinase inhibition attenuated the expected PTP-1B-increased expression. Conclusions. Our study suggests that Src kinase mediates a hypoxia-induced increased PTP-1B expression.